'If I'm not real, I'm Not Having an Impact': Relationality and Vicarious Resistance in Complex Trauma Care. (16th March 2022) - Woodlock, Delanie; Salter, Michael; Conroy, Elizabeth; Burke, Jackie; Dragiewicz, Molly
Abstract: There is growing commitment to trauma-informed practice and increased recognition of risks associated with this work. However, the benefits of working with trauma-affected clients are under-studied. Drawing on interviews with sixty-three welfare, health and legal professionals in Australia, we consider the salutogenic dynamics of work with women with experiences of complex trauma. Participants articulated an ethics of care in which professionals ally with clients against abuse and violence as well as transactional neoliberal service models. We identify this approach to trauma work as a form of vicarious resistance that challenges dichotomies of vicarious trauma and resilience. Abstract : Trauma-informed practice is becoming more common amongst front line workers. Acknowledgement of the risks associated with working with traumatised clients is also increasing. This article uses interviews with sixty-three front line workers to investigate trauma workers' experiences. We found that effective trauma practice is underpinned by an ethics of vicarious resistance that challenges transactional neoliberal service models. This vicarious resistance enriches understandings of vicarious traumatisation and vicarious resilience in trauma work.